Should we talk about the weather? How party competition and coalition participation influence parties' attention to economic issues. (November 2020) - Goldring, Edward; Park, Brandon Beomseob; Williams, Laron K
Media narratives of political campaigns paint a complex picture of parties carefully selecting communication strategies in response to the current social and economic climate as well as the strategic choices made by rival parties. Current empirical efforts based on simple ordinary least squares, however, fail to honor those complexities. We argue that ignoring the spatial and temporal dynamics at play produces misleading inferences about parties' behavior. In an application of German parties' attention to economic issues in official communications, we demonstrate that once scholars test the theories with a method that honors the inherent complexity of the process, the inferences about parties' degree of responsiveness change. Indeed, proper specification of the model shows that scholars who ignore spatial dependence tend to overstate the degree to which parties are responsive to changing conditions (such as public opinion or economic indicators) and understate the role of other constraints. Most notably, we find that parties have varying levels of path dependence, parties emulate the strategies used by ideological neighbors, and coalition partners appear to coordinate their strategies. These findings have implications for understanding variation in parties' messaging strategies and how voters perceive parties' positions.